Bacterial and methanogenic archaeal community changes during treatment of palm oil mill effluent and biological indicators for final discharge - Mohd Nor, Diana (2019)
The sustainable practice in the palm oil industry which supplies the most demanded edible oil in the world, has a long way to be well developed. One of the most challenging problems is the management of wastewater generated from the oil palm processing, known as palm oil mill effluent (POME). The most popular treatment method applied to treat POME in the palm oil mills is anaerobic ponding system. Bioconversion of POME to generate methane gas via anaerobic digestion involves a consortium of microbes which are responsible in several steps of the biodegradation process. However, the biodegradation potential of the microorganisms in the full-scale treatment system in the palm oil mill is yet to be explored. POME is also known to have the adverse environmental effects if it is not properly treated, including contamination of land and aquatic ecosystem and the loss of biodiversity. A proper treatment is needed to ensure POME can be discharged into the nearby river water or land according to the requirement set by the authority. However, the current monitoring system using physicochemical characterisation is not sensitive enough to indicate the actual source of contamination in the water bodies.